PERAN WATTPAD DALAM MENINGKATKAN KETERAMPILAN MEMBACA DAN MENULIS PADA PEMBELAJARAN SASTRA - Ayunda Nuril Chodiyah; Udjang Pairin; Titik Indarti (Universitas Negeri Makassar, 2024)
This study aims to describe the impact of using Wattpad on reading and writing skills, especially in learning literature in Indonesian language subjects at school. This descriptive qualitative research uses a literature study method with research data in the form of secondary data relevant to the topic under discussion. The data taken comes from books, encyclopedias, and research articles that have been published in national journals. The data collection procedure used in this research uses Mary W. George's literature theory with comparative data analysis techniques to identify comparisons of each relevant research to gain new insights into research on the use of Wattpad media. The results of this study show that the use of the Wattpad application has a role as a medium that can motivate students to learn literature. This is important because, in addition to improving students' reading and writing skills, learning becomes more lively, and students have their own pride because when they publish their writing, they are considered to have works that can be read by peers and all Wattpad users.